Linear and whorled nevoid hypermelanosis. - Goyal, Shivam; Shenoi, Shruthakeerthi D. (European Journal of Pediatric Dermatology, 2020)
Linear and whorled nevoid hypermelanosis is a congenital disorder mostly sporadic and rarely associated with mosaic trisomy of 7, 14, 18, 20 and X chromosome (1). It presents as widespread streaky hyperpigmented macules along Blaschko’s lines mostly on the trunk and limbs and do not cross the midline. The usual onset is within first few weeks of life with progression during the initial years of life. However, the pigmentation can gradually fade with time. Few cases are associated with developmental and growth delay, facial and body asymmetry, ventricular septal defects (2) and pseudohermaphroditism (1). The diagnosis is confirmed by histopathology which reveals increased pigmentation of the basal layer in absence of pigment incontinence.